2002
DOI: 10.1016/s0015-0282(02)04202-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of highly purified urinary follicle-stimulating hormone on oocyte and embryo quality

Abstract: Objective:To determine the effects of ovarian stimulation with highly purified urofollitropin on oocyte and embryo quality. Main Outcome Measure(s):Primary end points were number of morphologically mature oocytes retrieved, embryo quality, and pregnancy and implantation rates. Secondary end points were: total number of days of FSH stimulation, total dose of gonadotropin administered, fertilization rate per number of retrieved oocytes, embryo cleavage rate, live birth and miscarriage rates, endometrial thickne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 53 publications
0
19
0
1
Order By: Relevance
“…However, recent reports demonstrate that urinary FSH is considerably better than recombinant FSH in terms of oocyte and embryo quality and pregnancy and implantation rates, although the number of retrieved oocytes is higher in favour of rFSH [13][14][15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent reports demonstrate that urinary FSH is considerably better than recombinant FSH in terms of oocyte and embryo quality and pregnancy and implantation rates, although the number of retrieved oocytes is higher in favour of rFSH [13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the efficacy of rFSH compared to uFSH in terms of oocyte and embryo quality has been evaluated, and the results reported are highly in favour of urinary FSH. Some authors have attributed the difference to the presence of LH activity in the urinary FSH preparation which has a positive effect on oocyte maturation and embryo quality [13][14][15], while others assume that the difference between rFSH and uFSH may reside in the nature of FSH isoform activities [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the efficacy of recombinant FSH was compared with hFSH in terms of oocyte and embryo quality, and reported results were highly in favor of hFSH. Some investigators have attributed the difference to the presence of LH activity in the hFSH preparation, which has a positive effect on oocyte maturation and embryo quality (9)(10)(11), while others have assumed that the difference between recombinant FSH and hFSH may reside in the nature of FSH isoform activities (5,11). Gonadotropin isoforms influence a variety of biological activities, including cellular growth and development, steroidogenesis, and protein synthesis (12)(13)(14).…”
mentioning
confidence: 99%
“…In addition, the investigators found that patients treated with HP-hFSH used a significantly lower total amount of medication than those treated with rFSH. Selman et al (12) found that in women under 39 undergoing IVF, there was no statistically significant difference in pregnancy rate for women randomized to HPhFSH compared with women randomized to rFSH (delivery per embryo transfer of 39.7% versus 30.8%) and a higher grade 1 embryo score in the HP-hFSH group. A recently published study found a higher pregnancy rate in volunteers randomized to the combination of HP-hFSH and rFSH compared with those randomized to rFSH alone (13).…”
Section: Discussionmentioning
confidence: 99%